2001
DOI: 10.1303/aez.2001.329
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cold hardiness and northward invasion in the great mormon butterfly, Papilio memnon L. (Lepidoptera: Papilionidae) in Japan.

Abstract: To investigate factors involved in the recent northward invasion of the great mormon butterfly, Papilio memnon L. (Lepidoptera: Papilionidae), cold hardiness of pupae was compared among 4 populations including those in a subtropical and a northernmost area of Japan. The mean supercooling points (SCP) of diapausing and non-diapausing pupae were lower than Ϫ20°C in all populations. The SCP was not affected by an acclimation period nor by pupal weight, although it became higher with inoculation. Diapausing pupae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…On the other hand, the larval developmental time and pupal cold hardiness did not differ between forms in Japanese populations of the papilionid P . memnon (Yoshio & Ishii ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the larval developmental time and pupal cold hardiness did not differ between forms in Japanese populations of the papilionid P . memnon (Yoshio & Ishii ).…”
Section: Discussionmentioning
confidence: 99%
“…SCP of the pupae was measured using the procedure of Yoshio and Ishii () at 5, 15, 30, 45 and 60 days after pupation. The pupae were cooled at a rate of about 1–2°C/min, and the body temperature was recorded every second by a data logger.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that several Japanese butterflies are spreading their distribution range northwards, probably in association with the global warming (Parmesan et al . 1999; Yoshio & Ishii 2001; Yoshio 2002). Considering that B‐type butterflies are more adapted to warm climate than Y‐type butterflies (Kato & Handa 1992; Kato et al .…”
Section: Discussionmentioning
confidence: 99%
“…By evaluating the lower lethal temperature and winter survivorship around the range edge, Crozier (2003Crozier ( , 2004 reported that winter warming in the northeast USA was a prerequisite for the northward range expansion of a skipper butterfly, Atalopedes campestris. In Japan, the relationship between the physiological limit to low temperature and recent winter warming was investigated in terms of the northward range expansion of the great mormon butterfly, Papilio memnon (Yoshio & Ishii 2001), the flower bug, Orius strigicollis (Shimizu et al 2001), and the southern green stink bug, Nezara viridula (Kiritani 2006;Musolin 2007). Evidence that winter warming affects the local abundance of species within their distribution range rather than the extent of their distribution remains scarce.…”
Section: Discussionmentioning
confidence: 99%